Analisis Minat Belajar Siswa Pada Pembelajaran IPA Kelas 4 di Sekolah Dasar Negeri 066054 Kec. Medan Denai T.A 2022/2023 - Ramadani, Nurul; Ananda, Lala Jelita; Rangkuti, Irsan; Simanjuntak, Eva Betty; Manurung, Imelda Free Unita (Universitas Labuhanbatu, 2023)
This study aims to: (1) find out how students' interest in learning science class IV at SDN 066054 Kec. Medan Denai Field. The type of this research is descriptive research with a qualitative approach. The subjects in this study were 21 grade IV students and the homeroom teacher of grade IV. The research instruments used were questionnaires, interviews and documentation. The results showed that 39% of students felt that they enjoyed learning science, 29% of students were less interested in learning science, 27% of students paid less attention to learning science and 36% of students lacked involvement in learning science. Based on the results of the study that students' interest in learning science with an overall average indicator of interest in learning was 62% in the category of